Invasive and non-invasive electrodes for successful drug and gene delivery in electroporation-based treatments - Malyško-Ptašinskė, Veronika; Staigvila, Gediminas; Novickij, Vitalij (Frontiers in Bioengineering and Biotechnology, 2023)
Electroporation is known as an effective physical method for irreversible or reversible permeabilization of biological cells membranes, which is typically used for tissue ablation or targeted drug/DNA delivery into living cells. In cancer treatment context the full recovery due to electroporation-based procedure is frequently dependent on the spatial distribution /homogeneity of electric field in the tissue, therefore, the structure of electrodes/applicators plays a major role. This paper focuses on analysis of electrodes as well as in silico models, used for electroporation in cancer treatment and gene therapy. We reviewed various electrodes used for electroporation, analyzed the spatial electric field distribution using finite element method analysis, evaluated parametric compatibility, pros and cons of application, summarized options for improvement. Additionally, this review highlights the importance of tissue bioimpedance for accurate treatment planning using numerical modelling and the effects of frequency on the conductivity and permittivity values of the tissue